The Effectiveness of Management Information Systems in Crisis Management Strategy and Business Continuity - Rizky Nur Aji Setyawan; Muhammad Reza Herfianza Putra (Denasya Smart Publisher, 2025)
Management Information Systems (MIS) play a crucial role in supporting crisis management strategies and business continuity in today's complex digital era. This study aims to analyze the effectiveness of MIS in facilitating decision-making during crises and identifying components that influence its successful implementation. The methodology employs a quantitative approach through surveys based on the DeLone and McLean success model. The findings reveal that MIS contributes to early risk detection, real-time data integration, and improved operational efficiency. Additionally, MIS ensures data security, enhances inter-departmental coordination, and supports business growth post-crisis. By fostering employee training, integrating artificial intelligence technologies, and adapting to regulatory changes, MIS can be optimized to enhance organizational competitiveness. This research provides strategic insights into the importance of sustainable investment in MIS for future business resilience and innovation